(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The present research focuses on studying the effect of the geometric shape of the redistribution of spaces between the internal columns on the behavior of reinforced concrete structural frames exposed to explosive load, and the evaluation of the damage caused by that load on the structures. The eight-story reinforced concrete structure and three bays are designed according to the American Code ACI-14. SAP2000 (V.20) was used for analysis, design and study of the elastic – plastic structural response under the blast loads, through several variables, including the maximum lateral and plastic displacements, the number and condition of the formed plastic hinges, and index damage. The two-dimensional structural element was represented by a three-degree of freedom (beam-column) model, where the interaction between the axial force and the moment was used as a yield surface to follow the transition from elastic to plastic behavior for the columns, while the yield moment was defined as a yield criterion for the same behavior according to the principle of accumulated plasticity (Plastic Hinge) at the end of element. The uniformity in the column spacing, for a geometrical shape considerations, having a clear effect on reducing the deformations and plastic displacements of the structure and reducing the damage index with respect to the energy dissipated after the structural response. As a result, the distance between the mass and stiffness centers of the structural members affect the response of frame, the least distance between these two centers results in least damage to the structural elements compared to other symmetrical cases.